Cardiovascular risk factors and outcomes in COVID-19: A hospital-based study in India - Arvind K. Sharma; Vaseem Naheed Baig; Sonali Sharma; Gaurav Dalela; Raja Babu Panwar; Vishwa Mohan Katoch; Rajeev Gupta (Public Library of Science (PLoS), 2022)
Background & objectives Presence of cardiovascular (CV) risk factors enhance adverse outcomes in COVID-19. To determine association of risk factors with clinical outcomes in India we performed a study. Methods Successive virologically confirmed adult patients of COVID-19 at a government hospital were recruited at admission and data on clinical presentation and in-hospital outcomes were obtained. The cohort was classified according to age, sex, hypertension, diabetes and tobacco use. In-hospital death was the primary outcome. Logistic regression was performed to compared outcomes in different groups. Results From April to September 2020 we recruited 4645 (men 3386, women 1259) out of 5103 virologically confirmed COVID-19 patients (91.0%). Mean age was 46±18y, hypertension was in 17.8%, diabetes in 16.6% and any tobacco-use in 29.5%. Duration of hospital stay was 6.8±3.7 days, supplemental oxygen was in 18.4%, non-invasive ventilation in 7.1%, mechanical ventilation in 3.6% and 7.3% died. Unadjusted and age-sex adjusted odds ratio(OR) and 95% confidence intervals(CI) for in-hospital mortality, respectively, were: age ≥60y vs <40y, OR 8.47(95% CI 5.87-12.21) and 8.49(5.88-12.25), age 40-59y vs <40y 3.69(2.53-5.38) and 3.66(2.50-5.33), men vs women 1.88(1.41-2.51) and 1.26(0.91-1.48); hypertension 2.22(1.74-2.83) and 1.32(1.02-1.70), diabetes 1.88(1.46-2.43) and 1.16(0.89-1.52); and tobacco 1.29(1.02-1.63) and 1.28(1.00-1.63). Need for invasive and non-invasive ventilation was greater among patients in age-groups 40-49 and ≥60y and hypertension. Multivariate adjustment for social factors, clinical features and biochemical tests attenuated significance of all risk factors. Conclusion Cardiovascular risk factors, age, male sex, hypertension, diabetes and tobacco-use, are associated with greater risk of in-hospital death among COVID-19 patients.